“Like the Scum of a Torrent”: When Exactly Will Muslims Fit This Prophetic Metaphor? (American Journal of Islam and Society, 2014)
The hadith compilations are filled with the Prophet’s prophecies and predictionsabout the future, be it the future state of Muslims, the outcomes of battles,the signs of the end times, and so on. If Muslims are uncertain as to how andwhen some of these may come to pass, there is little doubt that, somehow,someway, they will certainly do so. Muslims’ confidence in the latter scenariostems from their unflinching belief in Muhammad as God’s messenger.The Sunan Abī Dāwūd, one of six authentic Sunni hadith collections, containsa hadith in which the Prophet predicts that one day Muslims, as a group,will be so weak and insignificant that other nations (umam) will compete tosnatch them, just like feeding animals (akalah) challenge one another overthir feed (qaṣ‘ah; lit.: large bowl). He insists that this will not be due to theMuslims’ smaller numbers, because their numbers will be huge; rather, theywill be as worthless as “the scum of a torrent” (ghuthā’ al-sayl), which is unworthyof being kept for any future use and thus deserves to be removed anddiscarded. At this time, the hadith continues, non-Muslims will have not oneiota of fear and apprehension (mahāba) of Muslims, but the latter will havealready resigned themselves to their own feebleness (wahn) and thus begripped with fear of non-Muslims ...